Assessment of physical activity and sedentary behaviour in bachelors of computer science students using global physical activity questionnaire version 2: a cross-sectional study - Shah, Juhi Nilesh; Berry, Aditi Ketkar (International Journal Of Community Medicine And Public Health, 2020)
Background: Physical activity has been determined as primary prevention strategy against 35 chronic conditions. Lack of physical activity, improper diet and increase in the use of computer has various health hazards. Considering that the bachelor of computer science students will mostly have sedentary work profile, once they enter the professional world, the objective of the present study was to assess their physical activity level using global physical activity questionnaire (GPAQ) version 2. Methods: A cross sectional study was conducted on 355 participants, 244 males and 111 females, from an institution catering bachelors of computer science course using GPAQ questionnaire. The data was analyzed to see if they meet the criteria set by World Health organization (WHO) and were classified into categories on basis of MET minute/week. The average time spent in sitting position was also calculated. Results: At work, 19.15% study participants were moderately active; in travel domain 64.5% were active, in leisure domain 43.94% were vigorously while 41.4% were moderately active. 73.23% of study participants met the WHO set criteria. 26.76% participants were inactive, 62.53% low active, 10.14% moderate active while only 0.81% was highly active. Average time spent in sitting was around 9 hours. Conclusions: Even though 73.23% of study participants met the criteria, most of the participants had low level of physical activity, thus there is huge scope for improvement in it. They also need to be educated regarding the risks of sedentary behaviour which will further help to reduce the hazards related to physical inactivity.